Berlin diary : the journal of a foreign correspondent, 1934-1941 - Shirer, William L. (William Lawrence), 1904-1993. (Baltimore, Md. : Johns Hopkins University Press, 2002)
In 1941 CBS radio broadcaster William L. Shirer published his diary he had kept in Europe during the 1930s -- specifically those sections dealing with the collapse of the European democracies and the rise of Nazi Germany. The book was an instant success, and it became the frame of reference against which thoughtful Americans judged the rush of events in Europe.
Foreword to the Johns Hopkins edition -- Foreword to the original edition -- Pt. I. Prelude to war -- Pt II. The war.
Originally published: New York : Alfred A. Knopf, 1941.
Includes index.
Keywords: Hitler, Adolf, -- 1889-1945.; Shirer, William L. -- 1904-1993.; World War, 1939-1945 -- Germany; World War, 1939-1945 -- Personal narratives, American; Europe -- Politics and government -- 1918-1945.; Germany -- Politics and government -- 1933-1945.